2023
DOI: 10.1177/00307270231195641
|View full text |Cite
|
Sign up to set email alerts
|

Plant breeding is needed to meet agroecological requirements: Legume crops as a case study

Diego Rubiales

Abstract: Legume-based cropping systems are regaining interest due to the environmental services and the variety of food and feed uses they provide, this having special interest in agroecological systems. There are many legume crops that can be adopted but focused breeding is needed to better meet the specific requirements of each system, especially in the situation of changing climate and often stressful environments. Standard breeding methods remain valid, from classical selection, to genomic assisted-breeding, profit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 130 publications
(140 reference statements)
0
0
0
Order By: Relevance
“…Thus, by not growing legumes locally, we continue to lose the ecosystem services they provide [8]. The solution can only be to develop cropping packages that make the crops profitable to farmers by adjusting cultivation techniques and developing adapted varieties [5,[9][10][11].…”
Section: The Key Role Of Legumes In Cropping Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, by not growing legumes locally, we continue to lose the ecosystem services they provide [8]. The solution can only be to develop cropping packages that make the crops profitable to farmers by adjusting cultivation techniques and developing adapted varieties [5,[9][10][11].…”
Section: The Key Role Of Legumes In Cropping Systemsmentioning
confidence: 99%
“…In the case of legumes, progress in broomrape resistance breeding has been slow, as they are rather minor crops in which relatively little has been invested in the last half century [5,9,100]. Most studies on broomrape resistance in legumes have concluded that there is low heritability and that inheritance is complex, highly influenced by the environment.…”
Section: Genetic Basis Of Resistancementioning
confidence: 99%